One-port nonlinear electric circuit for simulating grounding systems under impulse current - Correa Altafim, Ruy Alberto; Goncalves, Luiz [UNESP]; Pisani Altafim, Ruy Alberto; Creppe, Renato Crivellari [UNESP]; Piantini, Alexandre (Elsevier B.V., 2016)
A one-port nonlinear electric circuit to simulate grounding systems behaviors under high impulse currents is presented. The circuit is based on Loboda's and Pochanke's equations, which describe nonlinear behaviors of soil ionization phenomena. One of the major features of this nonlinear circuit is the possibility to simulate both ionization regions (linear and nonlinear) as a complete grounding system, in commercial simulation software such as Pspice, WorkBench (R), ATP or EMTP. In order to determine the linear and nonlinear circuit parameters, two known impulse current curves i(t) were applied on scale models and the corresponding impulse voltages U(t) were measured. From these circuit parameters, the U(t) x i(t) experimental curves were compared with one-port simulated results and the similarities, evaluated using the Area Under Curve (AUC) method, varied in the range 92-99%. In order to compare simulations with experimental data, a field circuit was elaborated to test three experimental scale models using single rods of different lengths. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Grounding; Impulse impedance; Impulse current; Electric circuit simulation